ANALISA PEMANTAPAN MUTU INTERNAL TAHAP PRA-ANALITIK PEMERIKSAAN HEMATOLOGI - Bastian Bastian; Aziyo Kurniawan; Aristoteles Aristoteles (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Stages pre-analytic are stages beginning in an inspection laboratory. Errors on stage pre-analytic account for 70% of frequent errors in the laboratory. To anticipate errors, the so-done effort stabilizes quality. To increase quality service and repair quality results. The Objectives: Is to stabilize internal quality during the pre-analytic stage of hematology in the laboratory at House Sick Type C, Palembang. Study this method is descriptive-quantitatvie with a purposive sampling technique in the officer laboratories â€œXâ€ and â€œYâ€, respectively total 15 respondents. Results: In the â€œXâ€ hospital laboratory has an average result of 96% and is said to be good, while in the â€œYâ€ hospital laboratory, it has an average 97% and is said to be good. That there is no significant difference between the second House Sick. Conclusion: Stabilization of internal quality stage pre-analytical inspection hematology on officers in the laboratories of Hospital â€œXâ€ and Hospital â€œYâ€ Palembang can be stated as good.